Automi, realtà virtuale e formiche Un'analisi della complessità del fenomeno bellico spaziale - Di Feo, Marzio (Premio Cesare Alfieri «Cum Laude», 2016)
Automi, realtà virtuale e formiche ("Automata, virtual reality and ants") proposes an analysis of the complexity of the war phenomenon through three different approaches: in the microphysics of the individual action, in simulated reality and in a metaphor with the biological environment. The investigation into the nature of the interactions between man and machine presents the attempt to dominate the Clausewitzian uncertainty of the battle through an automated, post-human system. This seems to be resolved in the Omega Point, which the theologian de Chardin had identified as a point of escape from entropy and from the disorder of reality. There is neither a scientific solution, nor a theological fate. Intelligence is shared through the semantics of the satellite, of the drone and through the information passing from machine to machine. While the warriors will act as a swarm, by sharing a huge amount of data, each one of them on the exocrine glands of the machine, St. Basil was right when he warned that whoever claims to speak on the nature of things (and therefore on war) should first of be able to speak of the nature of the ant.